Isolation, culture, and delivery considerations for the use of mesenchymal stem cells in potential therapies for acute liver failure - Yang, Hui; Chen, Jiaxian; Li, Jun (Frontiers in Immunology, 2023)
Acute liver failure (ALF) is a high-mortality syndrome for which liver transplantation is considered the only effective treatment option. A shortage of donor organs, high costs and surgical complications associated with immune rejection constrain the therapeutic effects of liver transplantation. Recently, mesenchymal stem cell (MSC) therapy has been recognized as an alternative strategy for liver transplantation. Bone marrow mesenchymal stem cells (BMSCs) have been used in clinical trials of several liver diseases due to their ease of acquisition, strong proliferation ability, multipotent differentiation, homing to the lesion site, low immunogenicity and anti-inflammatory and antifibrotic effects. In this review, we comprehensively summarize the harvest and culture expansion strategies for BMSCs, the development of animal models of ALF of different aetiologies, the critical mechanisms of BMSC therapy for ALF and the challenge of clinical application.